PENGARUH PERCEIVED USEFULNESS, CONFIRMATION, DAN SATISFACTION TERHADAP NIAT KEBERLANGSUNGAN PEMAKAIAN MOBILE INTERNET DI KALANGAN MAHASISWA (Fokus Ekonomi, 2010)
This study discussed the influence of post-adoption beliefs on the intention to continuance use of mobile Internet technology. Behavior to continue using a technology is strongly influenced by the fulfillment of someone's expectations after initial usage. This research tried to examine the influence of the perceived usefulness, confirmation, and satisfaction on continuance intention of use mobile Internet technology. Data collected with survei method from 110 students at public and private university in Purwokerto were examined by Partial Least Square with SmartPLS 2.0 software. The results presented that perceived usefulness, confirmation, and satisfaction have significant impact on continuance intention of use mobile Internet.